Validation of the Early Warning and Response System (EWARS) for dengue outbreaks: Evidence from the national vector control program in Mexico. - David Benitez-Valladares; Axel Kroeger; Gustavo Sánchez Tejeda; Laith Hussain-Alkhateeb (PLoS Neglected Tropical Diseases)
Background During 2017, twenty health districts (locations) implemented a dengue outbreak Early Warning and Response System (EWARS) in Mexico, which processes epidemiological, meteorological and entomological alarm indicators to predict dengue outbreaks and triggers early response activities. Out of the 20 priority districts where more than one fifth of all national disease transmission in Mexico occur, eleven districts were purposely selected and analyzed. Nine districts presented outbreak alarms by EWARS but without subsequent outbreaks ("non-outbreak districts") and two presented alarms with subsequent dengue outbreaks ("outbreak districts"). This evaluation study assesses and compares the impact of alarm-informed response activities and the consequences of failing a timely and adequate response across the outbreak groups. Methods Five indicators of dengue outbreak response (larval control, entomological studies with water container interventions, focal spraying and indoor residual spraying) were quantitatively analyzed across two groups ("outbreak districts" and "non-outbreak districts"). However, for quality control purposes, only qualitative concluding remarks were derived from the fifth response indicator (fogging). Results The average coverage of vector control responses was significantly higher in non-outbreak districts and across all four indicators. In the "outbreak districts" the response activities started late and were of much lower intensity compared to "non-outbreak districts". Vector control teams at districts-level demonstrated diverse levels of compliance with local guidelines for 'initial', 'early' and 'late' responses to outbreak alarms, which could potentially explain the different outcomes observed following the outbreak alarms. Conclusion Failing timely and adequate response of alarm signals generated by EWARS showed to negatively impact the disease outbreak control process. On the other hand, districts with adequate and timely response guided by alarm signals demonstrated successful records of outbreak prevention. This study presents important operational scenarios when failing or successding EWARS but warrants investigating the effectiveness and cost-effectiveness of EWARS using a more robust designs.